Is Quorum Sensing Interference a Viable Alternative to Treat Pseudomonas aeruginosa Infections? - García-Contreras, Rodolfo (Frontiers in Microbiology, 2016)
Quorum sensing (QS) coordinates the expression of multiple virulence factors in Pseudomonas aeruginosa; hence its inhibition has been postulated as a new alternative to treat its infections. In particular, QS interference approaches claim that they attenuate bacterial virulence without directly decreasing bacterial growth and suggest that in vivo the immune system would control the infections. Moreover, since in vitro experiments performed in rich medium demonstrate that interfering with QS decreases the production of virulence factors without affecting bacterial growth it was assumed than in vivo therapies will minimize the selection of resistant strains. Therefore, the underlying assumptions towards an effective implementation of a successful quorum sensing interference (QSI) therapy for treating P. aeruginosa infections are that (i) QS only exerts important effects in the regulation of virulence genes but it does not affect metabolic processes linked to growth, (ii) the expression of virulence factors is only positively regulated by QS, (iii) inhibition of virulence factors in vivo do not affect bacterial growth, (iv) the immune system of the infected patients will be able to get rid of the infections, and (v) the therapy will be effective in the strains that are actively producing the infections. Nevertheless, for QSI in P. aeruginosa, substantial experimental evidence against the validity of most of these assumptions has accumulated during the past years, suggesting that a far better understanding of its virulence and its behavior during infections is needed in order to design truly solid QSI therapeutic alternatives to combat this remarkable pathogen.